Beveridge Plan (postcard) - Jones, W.
1944-02-21 1944 1940s 2 pages 289A, PLUMSTEAD HIGH ST S.E.18. Transport General Workers' Union Dear Sir, Are you supporting the BEVERIDGE PLAN? We demand that you use all your powers to see that this Measure is passed IN FULL and that every bit of it becomes the Law of the Land. We are doing our level best in factory and workshop to turn out the equipment needed by our husbands and brothers, and our friends in the fighting line. We request you to do your best and make sure that the freedom for which they are fighting becomes a fact. This freedom is the FREEDOM FROM INSECURITY AND WANT, and is OUR PEACE AIM. To achieve it the Beveridge Plan must be given all priority as the very minimum first step to better world. Yours faithfully, W. JONES 126/TG/377/1/1/106